Pengelolaan Keuangan Halal: Penerapan Ekonomi Syariah dalam Dunia Bisnis Modern - Hendri Kroniko (STIKes Ibnu Sina Ajibarang, 2023)
This article discusses the important role of Islamic economics in halal financial management and its impact on the modern business world. Through a qualitative approach, this study explores how the application of Islamic principles not only improves the welfare of the people but also creates an ethical and sustainable business environment. It is found that Islamic financial institutions play a central role in providing products and services that are in accordance with Islamic values, although challenges in terms of reputation and public trust remain obstacles. This study also highlights the importance of supportive promotion and effective education to improve public understanding of Islamic finance. With the increasing awareness and demand for halal financial products, this article shows the great potential of Islamic economics in contributing to global economic growth. The conclusion of this study emphasizes the need for collaboration between business actors, financial institutions, and the government to create a conducive ecosystem for economic development.